2004
DOI: 10.1212/01.wnl.0000137017.45065.3e
|View full text |Cite
|
Sign up to set email alerts
|

Sensory neuropathy in vasculitis

Abstract: Sensory neuropathy, regardless of symmetry, can be due to vasculitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 21 publications
2
19
0
1
Order By: Relevance
“…42 Motor as well as sensory fibers are usually affected, but sometimes there is pure sensory neuropathy. 4,15,25,28,43 Proximal reductions in amplitude due to pseudo-conduction blocks may be identified for up to 9 days in 10% to 25% of patients before loss of conduction from the infarcted distal nerve stump. 25,28 Some conduction blocks are more long-lasting yet reversible 44 and may be due to dysfunction of myelin versus fluctuating axonal ischemia.…”
Section: Testing Electrodiagnostic Studiesmentioning
confidence: 99%
“…42 Motor as well as sensory fibers are usually affected, but sometimes there is pure sensory neuropathy. 4,15,25,28,43 Proximal reductions in amplitude due to pseudo-conduction blocks may be identified for up to 9 days in 10% to 25% of patients before loss of conduction from the infarcted distal nerve stump. 25,28 Some conduction blocks are more long-lasting yet reversible 44 and may be due to dysfunction of myelin versus fluctuating axonal ischemia.…”
Section: Testing Electrodiagnostic Studiesmentioning
confidence: 99%
“…At the time of the diagnosis, most patients show signs of mixed neuropathy and liver and cardiac involvement may be present [53]. Vasculitis may rarely present with an isolated sensory neuropathy, but sural nerve conduction is commonly impaired, reflecting the involvement of large nerve fibres [54 ].…”
Section: Neuropathologic Investigationsmentioning
confidence: 99%
“…Pure sensory vasculitic neuropathy has been described but is rare [2,3]. Randomised controlled trial data is lacking, however treatment with various immunosuppressants has been suggested [1].…”
Section: Sirsmentioning
confidence: 99%
“…Distal, symmetric sensory neuropathy secondary to nonsystemic vasculitis [2] is rare but may show a benign course [3]. Randomised controlled trials of therapy in nonsystemic vasculitic neuropathy have not been carried out [3], but anecdotal case series suggest treatment with immunosuppressive therapies such as cyclophosphamide, azathioprine and steroids [1].…”
Section: Sirsmentioning
confidence: 99%
See 1 more Smart Citation